2022
DOI: 10.3390/ma15113762
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Experimental and Modeling of Fly Ash-Based Concrete

Abstract: The application of supplementary cementitious materials (SCMs) in concrete has been reported as the sustainable approach toward the appropriate development. This research aims to compare the result of compressive strength (C-S) obtained from the experimental method and results estimated by employing the various modeling techniques for the fly-ash-based concrete. Although this study covers two aspects, an experimental approach and modeling techniques for predictions, the emphasis of this research is on the appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…With the application of more and more fy ash concrete on high in-situ stress environment, it could be found that the stress wave in high in-situ stress environment led to the failure of fy ash concrete. In recent years, some scholars have begun to study the dynamic mechanical properties of fy ash concrete [19][20][21][22][23]. Zhang et al [24] conducted dynamic splitting tests on concrete with fy ash (contents of 0%, 5%, 10%, 15%, 20%, and 30%) and found that the dynamic splitting tensile strength of concrete with water-cement ratio of 0.45 and 0.6 reaches the maximum value when fy ash content is 10%.…”
Section: Introductionmentioning
confidence: 99%
“…With the application of more and more fy ash concrete on high in-situ stress environment, it could be found that the stress wave in high in-situ stress environment led to the failure of fy ash concrete. In recent years, some scholars have begun to study the dynamic mechanical properties of fy ash concrete [19][20][21][22][23]. Zhang et al [24] conducted dynamic splitting tests on concrete with fy ash (contents of 0%, 5%, 10%, 15%, 20%, and 30%) and found that the dynamic splitting tensile strength of concrete with water-cement ratio of 0.45 and 0.6 reaches the maximum value when fy ash content is 10%.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, regression methods may exaggerate the significance of some variables [ 37 ]. Methods based on artificial intelligence, such as supervised machine learning (ML), are amongst the most highly advanced modeling approaches employed in the current topic area [ 38 , 39 , 40 , 41 , 42 ]. These approaches simulate reactions based on input characteristics, and testing validates the yield models.…”
Section: Introductionmentioning
confidence: 99%
“…Concrete continues to be the most widely utilized manmade substance on the planet. Given the considerable environmental impact of cement production, research has concentrated on both reducing the impact on the environment and cost reductions for cement-based products [ 1 , 2 , 3 ]. The utilization of metakaolin (MK) as an additive or partial substitute for cement is a major area of research in the manufacture of concrete materials.…”
Section: Introductionmentioning
confidence: 99%